Aromaticity of the triplet states of corannulene and coronene. (11th November 2022) - Govorov, Dmitrii; Pitawela, Niroodha R.; Gudmundsdottir, Anna D.
Abstract: Sunlight‐driven photochemical reactions are an important tool for sustainable organic synthesis. However, compared with ground states, for which the effects of structure on properties and reactivity are well established, the understanding of excited states is limited. In particular, an improved understanding of aromaticity and antiaromaticity in excited states is necessary to develop strategic photochemical methods for synthesizing polycyclic aromatic compounds. Herein, using density functional theory (DFT)‐optimized structures, the ground singlet (S0 ) and lowest triplet (T1 ) states of coronene and corannulene were compared. Bond length analysis demonstrated that both triplet corannulene and triplet coronene bear a partial resemblance to benzene. Nucleus‐independent chemical shift (NICS(0), NICS(1.7)ZZ, NICS scans) and anisotropy of the induced current density (ACID) calculations were carried out to compare the induced magnetic currents in these molecules. This analysis demonstrated rather weak π‐conjugation and partial antiaromaticity in the S0 state of each molecule. In contrast, a combination of circular induced currents and pronounced antiaromaticity was found in the T1 state of each molecule. However, the T1 of corannulene exhibited higher stability, which should facilitate functionalization. Consequently, corannulene is considered more suitable for photochemical applications. Abstract : Anisotropy of the induced current density (ACID), nucleus‐independent chemical shift (NICS(0)), and natural spin charge calculations suggest that in the lowest triplet configuration, corannulene has less pronounced antiaromatic properties than coronene.